The colors in the film In the heart of the sea’s cinematography: A photographic watercolor - Andrade, Matheus (2024)
The work presents an analytical exercise on colors in the cinematography of the film In the Heart of the Sea (Ron Howard, 2015, USA). We discuss the presence of layers of color in the work's images, understanding this plastic element, applied by the photography direction, as a dramatic resource of utmost relevance to the narrative, which we call photographic watercolor. In the film, the colors exert a gradual movement of tones and hues as the plot develops, just like watercolor paint on a canvas. We used a flexible and multidisciplinary analysis methodology to point out how the reference method used by the film's photography director intertwined the images in their variety dimensions and the meanings of colors. Our study thus demonstrates characteristics of the cinematography of Anthony Dod Mantle, through the dexterity with which he handles colors in the cinema.